The Epidemiology of Hepatitis C in a Canadian Indigenous Population - Julia Uhanova; Robert B Tate; Douglas J Tataryn; Gerald Y Minuk (Canadian Journal of Gastroenterology)
BACKGROUND An estimated 1% to 1.9% of North Americans are infected with the hepatitis C virus (HCV). Although Indigenous peoples are considered to bear the highest burden, there are only limited data regarding the demographic features and epidemiology of hepatitis C in this population.